2014
DOI: 10.1177/107327481402100407
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, Diagnosis, and Management of Kikuchi-Fujimoto Disease

Abstract: Although KFD was described more than 40 years ago, the etiology of this disease remains unsolved. Infectious or autoimmune processes were proposed but have not been definitively confirmed. Clinical presentation with systemic B symptoms and adenopathy may lead to an erroneous diagnosis of malignant lymphoma. The introduction of modern methods into hematopathology, including immunohistochemistry, flow cytometry, and molecular clonality studies, has decreased the probability of misdiagnosis. Until reliable progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
138
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(143 citation statements)
references
References 63 publications
0
138
0
Order By: Relevance
“…It was first reported in 1972 by Kikuchi and Fujimoto, independently [2,3]. Following the initial descriptions of KFD in 1972, approximately 740 cases have been reported in the literature [4]. Of those cases, 593 (81%) were adult patients, and male to female ratio was 1:2 in adults, but young boys were more commonly affected than girls (1.4:1) [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first reported in 1972 by Kikuchi and Fujimoto, independently [2,3]. Following the initial descriptions of KFD in 1972, approximately 740 cases have been reported in the literature [4]. Of those cases, 593 (81%) were adult patients, and male to female ratio was 1:2 in adults, but young boys were more commonly affected than girls (1.4:1) [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Following the initial descriptions of KFD in 1972, approximately 740 cases have been reported in the literature [4]. Of those cases, 593 (81%) were adult patients, and male to female ratio was 1:2 in adults, but young boys were more commonly affected than girls (1.4:1) [4,5]. During the 1990's, researchers noted that women were affected four times more than men by this disease, and this female predominance attracted attention from the science community, however, recent reports from Eastern countries have suggested that the actual ratio is closer to 1:1 [1, [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the disease is unknown. 13 It usually presents as localized painful lymphadenopathy, most commonly in the cervical region with associated fever and leukopenia in up to 50% of patients. 11 Kikuchi disease almost always runs a benign course and resolves in several weeks to months.…”
Section: Kikuchi-fujimoto Diseasementioning
confidence: 99%
“…2 Less common symptoms include chills, night sweats, weight loss, arthralgia, and cutaneous manifestations. 2,5 Although the amount of weight loss is not mentioned in the literature, our patient had lost a significant amount of weight. This may be explained by lack of appetite due to an inflammatory response and release of cytokines.…”
Section: Case Reportmentioning
confidence: 99%
“…In severe cases, high-dose corticosteroids or hydroxychloroquine have been shown to be effective in rapid resolution of symptoms. 1,2,3,7 Due to its association with connective tissue disorders, patients should be evaluated for simultaneous or subsequent development of SLE. 8…”
Section: Case Reportmentioning
confidence: 99%